376. COVID-19 Severity in HIV+ Patients Receiving Tenofovir. (31st December 2020) - Homsi, Nora; Vermeulen, Kendra; Snyder, Mitchell; Cennimo, David J; Sonyey, Alexandra
Abstract: Background: Early in the COVID-19 pandemic, tenofovir (TAF/TDF) was identified as a potential agent for SARS-CoV-2 due to binding to RNA-dependent RNA polymerase similarly to remdesivir. This led to the hypothesis that TAF/TDF may be lessening the severity and improving outcomes of COVID-19 infection. COVID-19 Severity COVID-19 Infection Outcomes Methods: Patients were identified by searching for HIV infection and SARS-CoV2 PCR testing. Type of antiretroviral therapy (ART), CD4+ cell count, HIV viral load (VL), comorbidities, presenting symptoms, severity of COVID infection, and outcomes were analyzed. COVID disease was classified as mild, moderate, severe, or critical based on World Health Organization criteria. We primarily sought to determine the effect of TAF/TDF on the severity of COVID infection. The secondary endpoint was to determine the effect of low CD4 count and HIV VL on the severity of infection. Results: 39 HIV+ patients were tested at least once for SARS-CoV2 by PCR at VA NJ Health Care System. 18 of 39 patients were PCR positive. In those, common presenting symptoms included: fever (15/18), cough (7/18), and lethargy/fatigue (6/18). 16 of the 39 HIV+ patients' ART included TAF/TDF; 8 of 18 COVID+ and 8 of 21 COVID-. In the COVID- group, 2 patients had CD4 count < 200 cells/mm 3, 3 patients had HIV VL >200, and 19 of 21 had at least 1 comorbidity. In the COVID+ group, 3 had CD4 count < 200 cells/mm 3, none had detectible HIV viremia, and all but one had comorbidities. Of COVID+ infections, 7 were mild, 3 moderate, 8 severe, and 5 patients died. 4 of the 5 patients that did not survive were in non-TAF/TDF group. All 3 patients with CD4 count < 200 cells/mm 3 had severe disease. 6 out of 8 patients developed mild disease in TAF/TDF group vs. 1 out of 10 patients in non-TAF/TDF group. 1 out of 8 and 7 out of 10 patients had severe or critical disease in TAF/TDF vs non-TAF/TDF groups respectively. Conclusion: In this sample of 18 HIV+ patients with COVID-19 infection, patients receiving TAF/TDF were more likely to develop mild disease and have full recovery than those who were on TAF/TDF-free regimens (75% vs. 10% and 87.5% vs. 50%, respectively). Patients not on TAF/TDF-based regimens had a higher rate of developing severe and critical COVID-19 disease (40% vs. 0% and 30% vs. 12.5%, respectively). Disclosures: All Authors : No reported disclosures